Implementation of Policy for Islamic State Vocational School: A Legal Perspective on Challenges and Development - Fesal Musad; Mansyur Achmad; Rizari Rizari (Unissula, 2025)
This research focuses on the implementation of policy for organizing Madrasah Aliyah Kejuruan Negeri (MAKN) under the Ministry of Religious Affairs of the Republic of Indonesia, particularly at MAKN 02 in Ende from 2021 to 2024. The main goals of this study were to analyze the implementation of policy for organizing MAKN, identify obstacles in policy implementation, and develop a policy implementation model that can help improve vocational education delivery in the future. This study used a qualitative descriptive field approach, employing a single instrumental case study. Primary data were collected through in-depth interviews and non-participant observation, while secondary data were taken from documents and regulations. The study applied Edwards III’s framework, focusing on dimensions of communication, resources, implementer attitude, and bureaucratic structure, and was enriched by adding policy feasibility to produce a more applicable policy implementation model. The results show that policy implementation at MAKN in Ende has not yet been fully effective due to limited resources, policy inconsistency, and a weak bureaucratic structure. The policy implementation model, which comprises policy feasibility, communication, resources, bureaucracy, and implementer loyalty, aims to help stakeholders implement vocational education policy more efficiently and effectively.